Pengaruh Budaya Organisasi, Motivasi, dan Pelatihan terhadap Kinerja Karyawan PT. Sinar Sosro Mojokerto dengan Komitmen Organisasi sebagai Variabel Intervening - Jefriel, Mochamad Miftakul; Halik, Abdul (Neolectura, 2025)
This study aims to analyse the effect of organisational culture, motivation, and training on employee performance with organisational commitment as an intervening variable at PT Sinar Sosro Mojokerto. In the face of increasingly fierce industry competition, companies are trying to improve the performance of human resources through strategies to strengthen organisational culture, increase motivation, and implement training programs. This research uses a quantitative approach with a survey method involving 78 respondents. Data were collected through questionnaires and analysed using Structural Equation Modeling (SEM) techniques to test the relationship between variables. The results showed that organisational culture, motivation, and training have a positive and significant effect on organisational commitment and employee performance. Organisational commitment acts as an intervening variable that strengthens the relationship between the independent variables and employee performance. This study provides practical implications for the management of PT Sinar Sosro Mojokerto in designing strategies to improve employee performance by strengthening organisational culture, motivating employees, and providing ongoing training programs.